2015
DOI: 10.1037/a0039506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple planning constraints on the development of grasp posture planning in 6- to 10-year-old children.

Abstract: This experiment examined how multiple planning constraints affect grasp posture planning in 6-to 10-year-old children (n ϭ 16 in each group) by manipulating the intended object end-orientation (left end-down, right end-down) and initial precision demands (standard, initial precision) of a bar transport task. Results indicated that grasp posture planning was strongly influenced by multiple planning constraints. During the standard condition the sensitivity toward comfortable final hand postures (end-state comfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 33 publications
(61 reference statements)
4
20
2
Order By: Relevance
“…Indeed, tests of children’s cognitive ability—inhibition with an Animal Stroop task, and planning with the Tower of London game—were positively correlated with performance on an end-state comfort task (Stockel & Hughes, 2015b). Although using different language to describe how a child chooses among grips, Stockel and Hughes (2015a) analysis agrees with Siegler’s (1996) model in postulating that competing strategies with various levels of strength lead to greater instability in behavior. Several researchers have proposed competing processes to explain how behavior changes over time.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, tests of children’s cognitive ability—inhibition with an Animal Stroop task, and planning with the Tower of London game—were positively correlated with performance on an end-state comfort task (Stockel & Hughes, 2015b). Although using different language to describe how a child chooses among grips, Stockel and Hughes (2015a) analysis agrees with Siegler’s (1996) model in postulating that competing strategies with various levels of strength lead to greater instability in behavior. Several researchers have proposed competing processes to explain how behavior changes over time.…”
Section: Discussionsupporting
confidence: 68%
“…The “goal-directed system” takes into account future requirements and if allowed will select the underhand grip. Stockel and Hughes (2015a) went on to show that when additional precision constraints to the initial grasp were added, reduced levels of the underhand grip were seen in all ages tested (6 to 10 years of age). They concluded that greater cognitive costs interfered with planning and increased the competition between the habitual and goal-directed systems.…”
Section: Discussionmentioning
confidence: 99%
“…Children, young adults, and older adults performed each task in three different movement contexts. Findings however, more recent work (e.g., Stöckel & Hughes, 2015), has observed 6-year-old children's motor planning was adult-like in their study. Stöckel and Hughes (2015) suggested that grasp postures of young children reflect a bias toward performing actions successfully executed in the past, due to cognitive demands outweighing available cognitive resources.…”
Section: Discussioncontrasting
confidence: 67%
“…Findings however, more recent work (e.g., Stöckel & Hughes, 2015), has observed 6-year-old children's motor planning was adult-like in their study. Stöckel and Hughes (2015) suggested that grasp postures of young children reflect a bias toward performing actions successfully executed in the past, due to cognitive demands outweighing available cognitive resources. With age, children are better able to integrate multisensory information to consider future demands and thus demonstrate action suitable for task which require second-order planning (Stöckel & Hughes, 2015).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation